Linderane Suppresses Hepatic Gluconeogenesis by Inhibiting the cAMP/PKA/CREB Pathway Through Indirect Activation of PDE 3 via ERK/STAT3 - Xie, Wei; Ye, Yangliang; Feng, Ying; Xu, Tifei; Huang, Suling; Shen, Jianhua; Leng, Ying (Frontiers in Pharmacology, 2018)
The role of phosphodiesterase 3 (PDE3), a cyclic AMP (cAMP)-degrading enzyme, in modulating gluconeogenesis remains unknown. Here, linderane, a natural compound, was found to inhibit gluconeogenesis by activating hepatic PDE3 in rat primary hepatocytes. The underlying molecular mechanism and its effects on whole-body glucose and lipid metabolism were investigated. The effect of linderane on gluconeogenesis, cAMP content, phosphorylation of cAMP-response element-binding protein (CREB) and PDE activity were examined in cultured primary hepatocytes and C57BL/6J mice. The precise mechanism by which linderane activates PDE3 and inhibits the cAMP pathway was explored using pharmacological inhibitors. The amelioration of metabolic disorders was observed in ob/ob mice. Linderane inhibited gluconeogenesis, reduced phosphoenolpyruvate carboxykinase (Pck1) and glucose-6-phosphatase (G6pc) gene expression, and decreased intracellular cAMP concentration and CREB phosphorylation in rat primary hepatocytes under both basal and forskolin-stimulated conditions. In rat primary hepatocytes, it also increased total PDE and PDE3 activity but not PDE4 activity. The suppressive effect of linderane on the cAMP pathway and gluconeogenesis was abolished by the non-specific PDE inhibitor 3-isobutyl-1-methylxanthine (IBMX) and the specific PDE3 inhibitor cilostazol. Linderane indirectly activated PDE3 through extracellular regulated protein kinase 1/2 (ERK1/2) and signal transducer and activator of transcription 3 (STAT3) activation. Linderane improved glucose and lipid metabolism after chronic oral administration in ob/ob mice. Our findings revealed linderane as an indirect PDE3 activator that suppresses gluconeogenesis through cAMP pathway inhibition and has beneficial effects on metabolic syndromes in ob/ob mice. This investigation highlighted the potential for PDE3 activation in the treatment of type 2 diabetes.